Spectrum of neurological disorders in pregnancy in a neurology clinic in eastern Uttar Pradesh - Singh, Pavan Kumar; Singh, Reeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pregnancy-induced endocrinal and physiological changes increase the risk of neuropathy and musculoskeletal problems in pregnancy. The purpose of this study is to provide a comprehensive look at the neurological and musculoskeletal disorders occurring during pregnancy. Methods: A total of 202 antenatal women with neurological and musculoskeletal problems were enrolled for study. Their demographic characteristics were noted. Detailed clinical history and neurological examination was done. Radiological investigations including x-ray, CT head, MRI brain, MRA, MR Venography with electrophysiological NCS studies were performed accordingly. Results: Among musculoskeletal symptoms most prevalent was LBA (50%), cramps (15.7 %) followed by pelvic girdle pain (10%) and wrist pain (8,5). Among peripheral neurological disorders most common was CTS (12.37%) followed by bells palsy. Among Central neurological disorders most common was headache (26.23%), seizures (12.37%), eclampsia (2.47%), followed by Cortical venous thrombosis CVT, BIH, PRES. Conclusions: Among musculoskeletal complaints the most frequent symptoms during pregnancy were low back pain, hip joint pain, cramps and wrist pain. Among neuropathies CTS prevalence was relatively higher in pregnant women especially in third trimester and was mostly bilateral. Among central neurological symptoms headache especially migraine without aura and seizures were common while eclampsia, CVT, BIH, PRES were less common.